HUBUNGAN ANTARA KEKUATAN OTOT TUNGKAI, KECEPATAN LARI, DAN PERCAYA DIRI TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SISWA EKSTRAKURIKULER FUTSAL SMP DAAR EL SALAM (Studi Korelasi Pada Siswa Ekstrakurikuler Futsal di Bogor) - Fajri, Muflikhul (Lentera: Jurnal Ilmiah Kependidikan, 2016)
This study aims to determine (1) Is there a relationship between leg muscle strength against dribbling skills on the futsal junior high school student extracurricular Daar El Salam. (2) Is there a relationship between the running speed of the dribbling skills on the futsal junior high school students' extracurricular Daar El Salam. (3) Is there a relationship between confidence in dribbling skills on the futsal junior high school students' extracurricular Daar El Salam. (4) Is there a relationship between leg muscle strength, running speed, and confidence together - equal to the dribbling skills on the futsal junior high school students' extracurricular Daar El Salam. Researchers using multiple correlations that examine the relationship with regression analysis techniques.These results indicate that there is a leg muscle strength correlation coefficient of 0.825 with a degree of relationship is very strong, there is a running speed correlation coefficient of 0.847 with a degree of relationship is very strong, and confident there is a correlation coefficient of 0.67 with a strong relationship level. Based on the test results and significance of linear simple regression equation between leg muscle strength, running speed, and confidence in dribbling skills of 0.939 with a coefficient of determination (R2) of 0.882 yaiu great effect amounted to 88.2%, while 11.8% is affected by the other factors that are not within the study variables. As well as the significance test for multiple correlation Fhitung 52.32 where the value is greater than the F table.